2022
DOI: 10.1093/cercor/bhac025
|View full text |Cite
|
Sign up to set email alerts
|

Differential auditory cortical development in left and right cochlear implanted children

Abstract: Unilateral aural stimulation has been shown to cause massive cortical reorganization in brain with congenital deafness, particularly during the sensitive period of brain development. However, it is unclear which side of stimulation provides most advantages for auditory development. The left hemisphere dominance of speech and linguistic processing in normal hearing adult brain has led to the assumption of functional and developmental advantages of right over left implantation, but existing evidence is controver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…Considering all the children with CI were right-sided implanted, there is a possibility that the laterality of neural activities was influenced by the implantation laterality. However, there was a study suggesting that cortical processing of speech showed no influence on the implantation side in children ( Wang et al, 2022 ). Thus, we postulated that the laterality of CI was not an essential factor for this result.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all the children with CI were right-sided implanted, there is a possibility that the laterality of neural activities was influenced by the implantation laterality. However, there was a study suggesting that cortical processing of speech showed no influence on the implantation side in children ( Wang et al, 2022 ). Thus, we postulated that the laterality of CI was not an essential factor for this result.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, fNIRS studies that used running speech as stimulus yielded conflicting results and did not assess speech-evoked activity longitudinally. Wang et al (2022) found no significant speech-evoked activity in either hemisphere for young pre-lingually deafened CI users directly after implantation and 1.5 months later, while Zhou et al (2023) reported larger bilateral activity compared to a NH control group in experienced pre-lingually deafened children with CIs. Bilateral speech-evoked activity in auditory areas was also observed in experienced pre-lingually deafened CI users of the same age as in the current study (Mushtaq et al, 2020), consistent with the current CI – T2 results.…”
Section: Discussionmentioning
confidence: 74%
“…The absence of this effect thus raises the question whether fNIRS is at all suitable for reliably detecting auditory cortex activity in paediatric subjects. Furthermore, changes in speech-evoked cortical activity were so far only assessed during the first few months after implantation (Petersen et al, 2013; Sevy et al, 2010; Wang et al, 2022) and it thus remains unclear if left-lateralised activity in pre-lingually deafened paediatric CI users might emerge with more CI experience. Additionally, only two fNIRS studies to date investigated the cortical processing of prosodic features in paediatric CI users (Chen et al, 2022; Wang et al, 2021) and neither of them reported the right-lateralisation of activity in response to prosodic modulations typically observed in NH infants (Homae et al, 2006; Homae et al, 2012; Telkemeyer et al, 2011) and children (Wartenburger et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Last, we removed hemodynamic signals, unrelated noise components, and unknown global deviations caused by respiratory, cardiac, and vascular movements or other experimental errors. The processed HbO signals ( Wang et al 2022 ) were then fitted to a general linear model which included regressors created by convolving a boxcar function for the five SNR conditions; the duration was equal to the average stimulus length of 20 sec. This part of the study involved an statistical parametric mapping hemodynamic response model.…”
Section: Methodsmentioning
confidence: 99%